2007
DOI: 10.1007/s11666-007-9107-7
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the Stabilization of α-Alumina on the Spray Process

Abstract: A phase change from a-alumina (corundum) in the feedstock powder to predominantly other alumina phases, such as c-alumina in the coating normally takes place, as a result of the spray process. It is expected that the prevention of this phase transformation will significantly improve the mechanical, electrical, and other properties of thermally sprayed alumina coatings. The results regarding the possibility of stabilization of a-alumina through addition of chromia published in the literature are ambiguous. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 17 publications
4
32
1
3
Order By: Relevance
“…It has also been reported that suppression of metastable phase formation, i.e., retention of the α phase is likely to improve the mechanical and other properties of the coating [5,7,8]. Hence, it is important to know the phase fractions of the alumina coatings form a technological point of view.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that suppression of metastable phase formation, i.e., retention of the α phase is likely to improve the mechanical and other properties of the coating [5,7,8]. Hence, it is important to know the phase fractions of the alumina coatings form a technological point of view.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature (e. g. [23]) it was shown that a mixing of oxide-ceramics depending upon the spraying conditions can be achieved. With conventional APS this is however not possible (e. g. [24]), presumably due to the small surface to volume ratio of the feedstock. Therefore the SPS process may be suitable, partic- ularly to mix a larger number of oxide ceramic systems in the plasma and to examine the resulting phases.…”
Section: Resultsmentioning
confidence: 99%
“…Thus plasma-sprayed alumina coatings cannot be used over 800 C. However spray conditions have been sought, which would keep the α phase. Stahr et al [146] have studied the stabilization of α alumina by spraying, with APS, WSP, and HVOF, mechanical mixtures of alumina and chromia, as well as pre-alloyed powders consisting of solid solution α-Al 2 O 3 with additions of Cr 2 O 3 . Stabilization of the α phase using the WSP process starting from mechanical mixtures was confirmed.…”
Section: Aluminamentioning
confidence: 99%